Antiphospholipid Syndrome in Patients with Venous Thromboembolism - Pengo, Vittorio; Denas, Gentian (Seminars in Thrombosis and Hemostasis, 2022)
Unprovoked (or provoked by mild risk factors) venous thromboembolism (VTE) in young patients, VTE in uncommon sites, or cases of unexplained VTE recurrence may be positive for antiphospholipid antibodies (aPL) and thus may be diagnosed with antiphospholipid syndrome (APS). The evaluation of aPL is standardized using immunological tests for anticardiolipin and anti-β2-glycoprotein I. The determination of functional antibodies (lupus anticoagulant) is less standardized, especially in patients on anticoagulant treatment. Patients positive for all the three tests are at high risk of recurrence, which, in turn, might lead to chronic obstruction of pulmonary vessels (chronic thromboembolic pulmonary hypertension). Randomized clinical trials have shown that triple-positive patients should be treated with vitamin K antagonists maintaining an international normalized ratio between 2 and 3. Whether patients with VTE and incomplete aPL profile can be treated with direct oral anticoagulants should be further investigated.
Keywords: Keywords